Regulation of microtubule nucleation mediated by γ-tubulin complexes - Sulimenko, Vadym; Hájková, Zuzana; Klebanovych, Anastasiya; Dráber, Pavel (Protoplasma, 2017)
The microtubule cytoskeleton is critically important for spatio-temporal organization of eukaryotic cells. The nucleation of new microtubules is typically restricted to microtubule organizing centers (MTOCs) and requires γ-tubulin that assembles into multisubunit complexes of various sizes. γ-Tubulin ring complexes (TuRCs) are efficient microtubule nucleators and are associated with large number of targeting, activating and modulating proteins. γ-Tubulin-dependent nucleation of microtubules occurs both from canonical MTOCs, such as spindle pole bodies and centrosomes, and additional sites such as Golgi apparatus, nuclear envelope, plasma membrane-associated sites, chromatin and surface of pre-existing microtubules. Despite many advances in structure of γ-tubulin complexes and characterization of γTuRC interacting factors, regulatory mechanisms of microtubule nucleation are not fully understood. Here, we review recent work on the factors and regulatory mechanisms that are involved in centrosomal and non-centrosomal microtubule nucleation.
Keywords: mikrotubuly; Microtubule-organizing centers; jaderný obal; Humans; Microtubules; proteiny asociované s mikrotubuly; Golgi Apparatus; Spindle pole bodies; Microtubule-Associated Proteins; Golgiho aparát; γ-Tubulin complexes; pólová tělíska vřeténka; Nuclear Envelope; centrozom; Non-centrosomal nucleation sites; multiproteinové komplexy; Centrosome; tubulin; Centrosomes; Microtubule nucleation; Multiprotein Complexes; lidé; Spindle Pole Bodies; Tubulin